Interpretation Levels in the Heritage of Rhetorical Thought (The International Journal for Scientific Research, 2023)
This study aims to show the interpretive thought of the masters of rhetoric, especially when explaining the summary, based on their interpretive pauses for time in Qur’anic texts in particular and linguistic contexts in general regarding the adverbial situation such as expressing the future in the past and vice versa. The study also embodies a condensed rhetorical interpretive document par excellence, taken from The Bride of Weddings and Al-Mutawil and Al-Awal to explain Al-Khatib Al-Qazwini’s summary as a model in the chapter on attribution and restriction by condition, to embody a model of rhetorical thought towards linguistic structures, their timing, and the elaboration of their meanings. It also attempts to highlight the method used in interpretation based on an assumption and its rebuttal or starting from the conclusion to the premise or vice versa, due to what distinguished the masters of the commentators of summary in terms of organized logic and philosophical thought, for which their counterparts - the owners of the literary rhetorical school - have always held them accountable for the stagnation and backwardness of rhetoric. In this study, there is proof and response to what is common among specialists in the study of linguistics in the West, that the Semitic languages, including Arabic, lack the indication of time with their verbs. Arabic has only two verbs, either completed or unfinished - from their point of view - as it does not care about the forms of the three verbs and their branches. This study, even if it is not specialized in temporal actions, nevertheless talks about time in multiple forms to prove and support that the language was able to embody time with words such as forenoon, sunrise, dawn, early morning, and morning, despite the difficulty in distinguishing between these times in many cases. In other languages, except with sentences and structures, it is not natural for a people to reach a sense of time and then have their words devoid of indication of the feeling in various places.
Keywords: Rhetorical Thought; Arabic Language; Interpretation; Linguistic Studies